Noms épithètes dans les expressions binominales - Martinho, Fernando (2017)
Adjectives have the exclusive property of being attributive nominal modifiers (or ‘epithets’). This exclusivity allows them to integrate the DP as modifiers of the lexical head N, while sharing, in Romance, its inflectional features. Some conversion models, however, allow the projection of a DP with two nominal heads in a modifying relation. Departing from previous proposals in Portuguese (Rio Torto 1998, Villalva 2003, Ranchhod 2003), our analysis implies that some N1N2 endocentric sequences, like «criança modelo» (child model) or “império fantasma” (empire ghost), in fact correspond to a modified structure, where N2 is an “attributive noun” (Martinho 2007). In these N1N2 “binominal modified constructions”, usually classified as cases of “adjunction”, we will consider, based on a corpus of cases from the CETEM database, that N2 appear to be a mixed category. Since N2 checks some basic adjectival properties (eg., N2 accepts multiple modification, predicative position and typical adjectival prefixation), we argue that this mixed category is equivalent to an adjectival modifier. Moreover, since N2 is only partially meeting these same properties (eg., N2 has no degree), we conclude that, in this kind of modification common to all Romance languages (Fabre 1996, Villoing 2002, Savary 2004 , Montermini 2006), the N2 nominal epithet is converted into a relational adjective (Demonte 1999).